Gerakan Pangan Murah (GPM) Terhadap Masyarakat Terdampak Bencana (Dinas Pangan Provinsi Sulawesi Tengah ) - Alhariri Abd Kadir; Fera Nayoam; Wiri Wirastuti (Institut Teknologi dan Bisnis (ITB) Semarang, 2023)
Natural disasters are events or series of events that threaten and disrupt people's lives which are caused by natural or non-natural factors, causing casualties, environmental damage, and much more. (Isa, 2016). The occurrence of natural disasters on the regional economy is of course very influential, especially in changes in food commodity prices. Food commodities are a basic need that is important for maintaining human survival. Food commodities have a very important role in economic, social and political aspects. However, in terms of the economy, food commodity prices in Indonesia often experience price changes, especially for disaster-affected areas. Price changes in food commodities are the biggest contributor to the inflation rate in Indonesia. one of the efforts made to control inflation is to carry out a work program, namely the